THE ROLE OF HIGHER EDUCATION IN IMPROVING WOMEN’S HEALTH - Jyoti; Rani, Anju (ShodhKosh: Journal of Visual and Performing Arts, 2024)
As the primary United Nations (UN) framework for achieving "integrated and indivisible" goals across the three distinctive components of sustainable development—the social, environmental, and economic—the 2030 Agenda for Sustainable Development entered into force in January 2016. Health and well-being are a social dimension and the third goal of SDG. Although men and women have different healthcare needs, both have a right to lead healthy lives. However, due to issues like scarce financial resources and travel constraints, gender prejudice continually prevents many women and girls from accessing health care. By 2030, the SDG aims to globally reduce maternal mortality to fewer than 70 per 100,000 live births. By 2030, make sure that everyone has access to family planning, information, education, and the inclusion of reproductive health into national plans and activities. Education is typically considered a resource at the individual level by health researchers. However, within social connections, education is probably both an intra-individual and an inter-individual health resource. The inclusion of personal hygiene teachings in the school curricula, as well as free and universal compulsory education, which has resulted in widespread literacy, has greatly increased women’s knowledge of health issues. In this paper, the main topic is the effect of education on women’s health. The amount of newborn and child mortality, maternal mortality, communicable and non-communicable diseases, and awareness of all types of health issues are significantly influenced by women’s education. Almost all of the other goals are influenced by health and education, which are the subjects of SDG 3 and SDG 4, which are both focused on health and well-being. For instance, universal health coverage (UHC) can help reduce poverty (SDG 1) by protecting individuals from a significant source of financial hardship, and good health can promote increased employment and economic growth (SDG 8). Strong healthcare systems can shield citizens from the negative social and financial effects of epidemics and other medical emergencies. Therefore, this essay aims to explain how higher education contributes to the long-term health and well-being of women in Haryana.